Transactions on Engineering Technologies International MultiConference of Engineers and Computer Scientists 2015 - Yang, Gi-Chul.; Ao, Sio-Iong.; Huang, Xu.; Castillo, Oscar; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2016)
This volume comprises selected extended papers written by prominent researchers participating in the International MultiConference of Engineers and Computer Scientists 2015, Hong Kong, 18-20 March 2015. The conference served as a platform for discussion of frontier topics in theoretical and applied engineering and computer science, and subjects covered include communications systems, control theory and automation, bioinformatics, artificial intelligence, data mining, engineering mathematics, scientific computing, engineering physics, electrical engineering, and industrial applications. The book describes the state-of-the-art in engineering technologies and computer science and its applications, and will serve as an excellent reference for industrial and academic researchers and graduate students working in these fields.
Real-Time Stabilization of a Single Inverted Pendulum Using A Power Series Based Controller; E.A.Kennedy, H.T.Tran -- A Support System for Developing Tourist Evacuation Guidance; N.Emori, T.Izumi, Y.Nakatani -- Delay Constraint CAC with Hierarchical DBA over GPON-LTE Converged Networks; I-S.Hwang, B-J.Hwang, AA.Nikoukar -- Exploring Critical Success Factors of Mobile Recommendation Systems: The End User Perspective; Y.Sun, W.K.Chong, K.L.Man, S.Rho, D.Xie -- Multimedia Management Services Based On User Participation with Collaborative Tagging; J.Park, K.W.Park, Y.Yun, M.Kim, S.Rho, K.L.Man, W.K.Chong -- Attenuation of Conducted and Radiated Electromagnetic Interference Generation in High-frequency Switching Devices; C.Jettanasen, P.Sripodok -- Involving End-Users in Web-based System Development with INTER-Mediator; M.Nii, K.Tei, F.Ishikawa -- Change Propagation in Software Product Lines Using ACP Algorithm; K.L.S.Soujanya, A.Rao -- The User View and the System View of Matching Sites for End-User-Initiative Development; T.Chusho -- Accelerating Image Deblurring Using Circulant Approximations; F.A.Fairag, A.M.Al-Mahdi -- Optimization of Synthesis Process of Nano-hydroxyapatite; D.E.Ledesma-Carrión -- The Effects of Welding Processes and Microstructure on 3 Body Abrasive Wear Resistances For Hardfacing Deposits; K. M. Kenchi Reddy -- Remanufacturing Strategies for Sustainable Development; S.S.Kuik, T.Kaihara, N.Fujii -- Real Numbers and Full Integration to Support the Lean Practice; C.Zuhara, M.Takefumi -- A Route Optimization Problem in Electrical PCB Inspections: Pickup and Delivery TSP-Based Formulation; H.Katagiri, Q.G.Guo, H.Wu, H.Hamori, K.Kato.
Keywords: Telecommunication; Control engineering; Robotics; Automation; Engineering mathematics; Engineering -- Data processing; Mathematical models; Software engineering; Mathematical physics; Communications Engineering, Networks; Control, Robotics, Automation; Mathematical and Computational Engineering Applications; Mathematical Modeling and Industrial Mathematics; Software Engineering; Theoretical, Mathematical and Computational Physics